EMERGÊNCIA E FLUXO DE INFORMAÇÃO EM REDES COMPLEXAS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
The emergence is a phenomenon that gives sense to the qualitative unity of any substance, consisting the reflex in the ontological act of perception. It is the conceptual key that justifies the use of complex network models to describe systems, which also are complex in nature. Given this key concept, it was desired to apply it on real objects in order to create new analysis methodologies. For this, graph’s theory and random walk’s theory were used as fundamentals for two study cases. One of them consists on an analysis of the mythological social network of Odyssey of Homer. It was found that this network displays structural characteristic of real social network mixed with fictional aspects associated to mythological characters. Another study was the oral tolerance phenomenon modeled as a complex network associated with stochastic dynamics. We applied the random walk as a way to understand the relative importance of each immunological component. Finally, it becomes evidenced that the key concept of emergence allows new forms of analysis using complex network theory as a model which comprises the complexity inherent on the conception of real systems.
Keywords: redes complexas; caminhada aleatória; mitologia comparada; tolerância oral; complex networks; random walk; comparative mythology; oral tolerance; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA